TUBERCULOUS ARTHRITIS OF THE ANKLE MIMICKING SYNOVITIS IN CHILD - A CASE REPORT - Erick Yudistira Christanto; Sulis Bayusentono (Journal Orthopaedi and Traumatology Surabaya, 2020)
Background: Extrapulmonary Tuberculosis is approximately 10% of all tuberculosis (TB) cases, and the musculoskeletal system’s involvement was only 2-4. The incidence of ankle TB was found to be less than 2% of all musculoskeletal TB. The rare occurrence, uncommon site, non-specific symptoms, lack of awareness frequently causes diagnosis difficulties.Case Report: A 2,5-year-old child came to the hospital with the main complaints of swelling and pain on the left ankle since one year ago. She was diagnosed with the ankle’s synovitis from the previous hospital and was given analgesics and a warm compress on the left ankle. However, the swelling of her left ankle increased during the last seven months, causing limitation of the left ankle movement, then she was admitted to the hospital for further examination.Discussion: Radiologic examination revealed peripheral osseous erosions, reduced bone mineral content, and soft tissue swelling. A Mantoux test was positive with 15 mm induration and 25 mm erythema. Anti-tuberculous drugs (ATD) therapy was given with isoniazid 50 mg, rifampicin 75 mg, pyrazinamide 150 mg, and ethambutol 230 mg for two months, as an intensive phase therapy following rifampicin 75 mg and isoniazid 50 mg for ten months.Conclusion: Tuberculous arthritis of the ankle poses a diagnostic-difficulties, it should be considered especially in the endemic area. It is often misdiagnosed with other musculoskeletal conditions, which can delay the initiation of appropriate treatment. TB must be confirmed by histological pathology. A combination of ATD and surgery can lead to clinical improvement.